Molybdophosphoric acid dispersed in modifed poly(vinyl alcohol) as catalysts for a-pinene hydration - Castanheiro, J (2012)
A PVA/HPMo membrane crosslinked with succinic acid was modified by treatment with acetic anhydride in order to improve its hydrophobic properties, and used as catalyst in the hydration reaction of a-pinene. The increase of membrane hydrophobicity with acetylation is documented not only by the water droplet contact angle but also by the sorption coefficients of a-pinene and water. The introduction of acetyl groups improves the membrane transport properties as reflected by pinene diffusivity calculated from permeation data.